Does Organic Crowding Out Influence Organic Food Demand? – evidence from a Danish micro panel - Lars Gårn Hansen; Laura Mørch Andersen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
All previous studies of organic food demand that investigating substitution focus on specific food submarkets and have to assume separability from other food consumption. However, consumers typically associate attributes such as e.g. healthiness and environment friendliness with organic variants of most types of food. If such general organic attributes are important for consumer behaviour then separability may not hold because the general attribute obtained from one type of organic food may be a close or even perfect substitute for the same attribute obtained from other types of organic food. In this paper we utilize a unique Danish micro panel where all food demand is registered on a disaggregated level with an organic/non-organic indicator to estimate a general food demand system with organic variants. We clearly reject the usual separability assumption and find that the behaviour of Danish consumers is consistent with them perceiving such general organic attributes. In addition estimation of a general demand system makes calculation of economy wide organic price elasticities and other insights into the structure of organic food demand possible.
Keywords: D12; 330; Organic consumption; crowding out; separability; AIDS model; home scan data